Analisis Keajaiban Kitab DalÃ¢il al-KhairÃ¢t Karya Al-Imam Al-Jazuli - Moh. Ali Ghafir (STAI Syaichona Moh. Cholil Bangkalan, 2020)
The purpose of this research is to find out the miracles contained in the book of Dalail al-Khairat and for its readers. This research usesed a literature research methodology on the Dalail al-Khairat book through content analysis. From the results of the research it was found that Dalail al-Khairat's miracle was obtaining legality and a diploma from the Prophet Muhammad sallallaahu alaihi wa sallam, a practice of many groups. Whereas the finding of miracles for readers is to guide the reader to success, many of the readers of Dalail al-Khairat have achieved wushul to Allah Almighty and they met the prophet while sleeping and in the real world.